Physical linkage preservation in DNA storage - Haussler, David; Rice, Brandon J (2023)
Disclosed herein are compositions, systems, kits and methods related to preserving physical linkage information of isolated DNA subject to DNA damage, and identifying a nucleic acid preservative. Physical linkage information and DNA integrity may be preserved by methods relating to reassembly of chromatin onto isolated DNA molecules so as to protect the nucleic acids, preserve physical linkage information, or size select molecules of interest. Nucleic acid compositions produced by methods disclosed herein are preserved so as to be analyzed, for example, by high throughput sequencing methods.